Sistem Informasi Penjualan Pada Cendana Digital Printing Station Menggunakan Metode FIFO - S, Andreas Rian Dwi; Februariyanti, Herny (LPPM UNIKA Santo Thomas Medan, 2023)
In the city of Semarang, there is a Cendana digital printing office. The problem faced by Cendana Digital Printing Station is the ever-increasing volume of data, both goods and customer data. The increasing number of sales transactions also added to the complexity of the problems faced by Cendana Digital Printing Station. As a result, the information needs of Cendana Digital Printing Station were not met accurately and quickly. In addition, errors often occur in determining the number of goods in the warehouse, which causes the sales department to make sales transactions even though the goods are actually not in the warehouse or not available. In addition, there are frequent delays in the preparation of reports and the provision of the necessary information, which causes a long time to be wasted. The research objective is to create a sales sysfo for Cendana Digital Printing Station related to sales transactions using the FIFO method in determining the stock of goods in the warehouse.